Community Structure Of Echinoderms In Aquatic Park Of Pieh Island West Sumatra - Kurniawan, Mohd Rizky; Nasution, Syafruddin; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in October-November 2016 at the Aquatic Park of Pieh Island, West Sumatra. The aim of research to determine the community structure of phylum Echinodermata which includes: density, diversity, uniformity species, dominance and importance indexs. The method used was survey method, location determined by purposive sampling. The locations were divided into three stations, Station I was located on the western side of the island, Station II was located in the Southeast side of the island and Station III was located in the eastern side of the Pieh island. There are six species found in the area: Echinothrix diadema, Diadema savignyi, Echinos discus, Acanthaster planci, Ophiothrix foveolata, Ophiothrix sp.. Ophiothrix foveolata Â and Echinothrix diadema were the most common in the area. Diversity (H ') was moderate condition and the value of a uniformity was high. The highest number of Echinoderms was found at depths of > 2 m. The dominan species were Echinothrix diadema and Ophiothrix foveolata.Â Key words: Ecinoderms, Community Structure, Pieh IslandÂ